The Influence of Teachers’ Pedagogical Competence on Education Quality: A Quantitative Study in Public Elementary Schools Gunem District Rembang Regency - Arifin, Ahmad Zaenal; Rasiman, Rasiman; Supandi, Supandi (FKIP - Universitas Riau, 2025)
Education quality in elementary schools is strongly influenced by the professional competence of teachers, particularly their pedagogical abilities. In Gunem District, Rembang Regency, disparities in education quality remain evident, with many schools still falling short of the expected standards. This study aims to examine the influence of teachers’ pedagogical competence on education quality in public elementary schools. Employing a quantitative explanatory design, data were collected through a proportional random sample of 106 teachers from a total population of 144. The main research instrument was a Likert-scale questionnaire, whose validity and reliability were confirmed through Pearson correlation and Cronbach’s Alpha tests. Data analysis was performed using simple linear regression with SPSS 25. The results indicate a positive and significant effect of teachers’ pedagogical competence on education quality, with a correlation coefficient of 0.630 and an R² value of 0.397. These findings highlight the importance of continuous professional development programs to strengthen teachers’ pedagogical competence as a key strategy for improving education quality in elementary schools.